Targeting SARS‐CoV‐2 RBD Interface: a Supervised Computational Data‐Driven Approach to Identify Potential Modulators. (4th September 2020) - Gulotta, Maria Rita; Lombino, Jessica; Perricone, Ugo; De Simone, Giada; Mekni, Nedra; De Rosa, Maria; Diana, Patrizia; Padova, Alessandro
Abstract: Coronavirus disease 2019 (COVID‐19) has spread out as a pandemic threat affecting over 2 million people. The infectious process initiates via binding of SARS‐CoV‐2 Spike (S) glycoprotein to host angiotensin‐converting enzyme 2 (ACE2). The interaction is mediated by the receptor‐binding domain (RBD) of S glycoprotein, promoting host receptor recognition and binding to ACE2 peptidase domain (PD), thus representing a promising target for therapeutic intervention. Herein, we present a computational study aimed at identifying small molecules potentially able to target RBD. Although targeting PPI remains a challenge in drug discovery, our investigation highlights that interaction between SARS‐CoV‐2 RBD and ACE2 PD might be prone to small molecule modulation, due to the hydrophilic nature of the bi‐molecular recognition process and the presence of druggable hot spots. The fundamental objective is to identify, and provide to the international scientific community, hit molecules potentially suitable to enter the drug discovery process, preclinical validation and development. Abstract : Finding hits for the Spike : Our computational studies on SARS‐CoV‐2 Spike protein receptor binding domain identified the N‐terminal region as a potential druggable hot‐spot. Herein, docking and pharmacophore HTS yielded a set of consensus molecules suitable for drug discovery screening. These compounds could represent lead molecules able to modulate the Spike‐ACE2 protein‐protein interaction, a putative intervention mark to discover therapeutics against SARS‐CoV‐2 pandemic.